Fixed Point Results for Geraghty Type Contractions in Extended Rec-tangular Fuzzy b-metric Space with an Application (Contemporary Mathematics, 2024)
The aim of this paper is to define the notions of extended fuzzy b-metric spaces, fuzzy rectangular b-metric spaces and extended fuzzy rectangular b-metric spaces and to establish certain fixed point results in these settings utilizing Geraghty type contractions. We also furnished an example which illustrates our main result. To show the authenticity of our results we provide an application involving fuzzy integral equation. The obtained results generalize many existing  results in the literature.
Keywords: extended b-metric space; fuzzy b-metric space; extended fuzzy b-metric space; fuzzy rectangular b-metric space; extended fuzzy rectangular b-metric space and fixed point theorems